(untitled) (AYUSHDHARA, 2017)
Objectives: The present study was carried out to evaluate the immunomodulatory efficacy of Karanja (Pongamia pinnata Pierre) Seed Churna in aqueous solution. Methods: The animals for this trial were rats of either sex and blood that was used was sheep’s blood. The study was conducted in three groups having 6 rats in each group. First group was control group and tap water was administered to this group orally, second and third group received the test drug aqueous solution at the dose 800mg and 4000mg/kg body weight respectively for 10 consecutive days. The test drug was evaluated for effect on humoral antibody formation, on cell mediated immunity and spleen and thymus weight gain. Histopathological studies were also performed on spleen and thymus in SRBC pre-sensitized rats. Results: The data on the effect of test drug on antibody formation against sheep red blood cells shows marginal statistically non-significant decrease in antibody titre at both lower and higher dose levels. Cell mediated immunity only at higher dose level in 48 hours reached statistically significant level whereas non-significant changes were observed in the weight of spleen and thymus. Conclusion: Karanja seed possess significant cell mediated immunity and non-significant effect on antibody formation and also non-significant effect on spleen and thymus weight gain.